T-cell receptor gamma delta and gamma transgenic mice suggest a role of a gamma gene silencer in the generation of alpha beta T cells. - Ishida, I (1990)
A T lymphocyte expresses on its surface one of two types of antigen receptor, T-cell receptor alpha beta or T-cell receptor gamma delta, encoded by a pair of somatically rearranged alpha and beta or gamma and delta genes. It has been suggested that alpha beta T cells are generated only from precursor T cells that failed to rearrange gamma and delta genes in a functional form. However, we found that transgenic mice constructed with functionally rearranged gamma and delta genes produce a normal number of alpha beta T cells. The transgene gamma present in these alpha beta T cells is repressed apparently through an associated cis DNA element (silencer). We propose that some T-cell precursors are committed to generate alpha beta T cells independent of the rearrangement status of their gamma gene and that this commitment involves activation of a factor(s) that interacts with the gamma gene-associated silencer.